Identification and prevalence of ectoparasites and endoparasites in kerandang fish Channa pleurophtalma and catfish Clarias batrachus captured from Sebangau River - Infa Minggawati; Frid Agustinus; Tania Serezova Augusta; Candra Putra Pahawang; Toto Francisco (Jurnal Akuakultur Indonesia)
ABSTRACT